Severe Hypocalcemia Occurring During the Hospitalization of a Patient Affected by Permanent Post-Surgical Hypoparathyroidism with Multimorbidity: A Case Report - Nardone, Isabella; Wolde Sellasie, Sium; Cinque, Alessandra; Tacchi, Giovanni; Zaccaria, Simona; Giusto, Cristina; Palumbo, Roberto; Gaspardone, Achille; Uccioli, Luigi; Amendola, Stefano (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
BackgroundPatients with permanent hypoparathyroidism experience an impaired quality of life, due to acute and chronic complications that may affect several organs, with an increased risk of hospitalisation and death. Adequate and continuous replacement therapy with calcium and calcitriol is necessary to avoid symptoms and long-term complications related to hypocalcemia.Case PresentationA 63 years old male, affected by permanent post-surgical hypoparathyroidism, was hospitalized in the cardiology department because of a dehiscence of the subcutaneous housing of the double-chambered implantable cardioverter-defibrillator. Chronic replacement therapy for hypoparathyroidism was poorly controlled and, during hospitalization, severe hypocalcemia occurred together with electrocardiographic and echocardiogram life-threatening alterations. Conclusion Constant and targeted long-term replacement therapy with calcium and particularly calcitriol is necessary to avoid major consequences on patients’ health, especially during acute events and in the presence of other comorbidities.
Keywords: calcitriol